The Profilization of Regions Innovative Development in the System of the Economic Space of the Russian Federation - Irina Danilova; Irina Savelieva; Irina Kilina; Anzhelika Karpushkina (Communications of International Proceedings, 2020)
There are the preservation of significant interregional differentiation and weak connectivity in the innovation sphere of Russian regions. This presupposes the study of the reserves of innovation dynamics: taking into ac-count the uniqueness of accumulated assets; comparative innovation advantage in resources, production and results of innovation; territorial location to relatively innovative growth centres. The authors propose a methodological approach for assessing the type of spatial environment of regions, which was tested on the example of subjects of the Russian Federation with a single-industry metallurgical specialization. The proposed approach is based on a set of indicators characterizing the socio-economic and innovative conditions of regional development, determining the spatial status of regions of the Russian Federation, assessing the connectivity between regions within the macro-zone. The types of local innovation spaces are highlighted using cases of macro-zones in mono-specialized regions, limiting or stimulating interregional cooperation; promising partners for innovative interaction have been identified. The spatial approach to assessing innovative development allows expanding understanding of potential drivers of growth, directions and organizational formats that activate the innovation dynamics of regions. A verbal model of the development of interregional innovative relations and a real case on the example of the regions "Chelyabinsk region - Sverdlovsk region", determined by the actual innovative conditions and results in the innovation sphere of the regions, are presented.
Keywords: Innovative Development of Regions; Innovative Space; Innovative Macro Zone; Regional Connectivity; Innovative Profile.